2011
DOI: 10.1111/j.1865-1682.2011.01270.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatalities in Wild Goats in Kurdistan Associated with Peste Des Petits Ruminants Virus

Abstract: Between August 2010 and February 2011, over 750 deaths were recorded among wild goats (Capra aegagrus, the endangered progenitor of the domestic goat) in Kurdistan. Based on the clinical signs and post-mortem findings, the involvement of peste des petits ruminants virus (PPRV) was suspected. This was confirmed by laboratory analysis, and the virus was found to be closely related to a Turkish strain isolated in 2000. During the outbreak in wild goats, no disease in domestic animals was reported. Domestic rumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 4 publications
2
46
0
Order By: Relevance
“…As expected, goats showed the typical moderate to severe clinical signs (trials 1 and 3) reported previously ( 7 9 ). Clinical signs in PPRV-infected sheep (trial 4) were generally mild to moderate, as previously described ( 3 , 8 ).…”
Section: The Studysupporting
confidence: 88%
See 1 more Smart Citation
“…As expected, goats showed the typical moderate to severe clinical signs (trials 1 and 3) reported previously ( 7 9 ). Clinical signs in PPRV-infected sheep (trial 4) were generally mild to moderate, as previously described ( 3 , 8 ).…”
Section: The Studysupporting
confidence: 88%
“…In 4 trials (trials 1–4; Table) we intranasally inoculated suids with a recent PPRV-LIV strain (Kurdistan/2011 [ 7 , 8 ]). Contact control animals were added 2 days later.…”
Section: The Studymentioning
confidence: 99%
“…In southwest Asia, it spread to China (Tibet Autonomous Region) in 2007 (Bao et al, 2008), the Maldives in 2009, and Bhutan in 2010. In Asia, the impact of PPR has increased in the last decade to such a point that regular epizootic activities resulted in spillovers in the wild population and large die-offs among different wild species, some of them being endangered, notably bharal in Tibet (Bao et al, 2011(Bao et al, , 2012, ibex in Pakistan (Abubakar et al, 2011), and wild goats in Kurdistan (Hoffmann et al, 2012). All events were related to PPR-infected livestock.…”
Section: Discussionmentioning
confidence: 96%
“…PPRV continues to spread across regions previously not affected [18]. Multiple outbreaks of PPR have occurred over the last ten years in Iran and neighbouring countries with devastating effects on the population of wild goats and sheep [19, 20]. PPR virus (PPRV) has also caused multiple deadly outbreaks in domestic small ruminants especially in western and north-central parts of Iran with significant economic losses [21, 22].…”
Section: Introductionmentioning
confidence: 99%